Using isotopes to incorporate tree water storage and mixing dynamics into a distributed ecohydrologic modelling framework. Issue 3 (25th February 2020) - Knighton, James; Kuppel, Sylvain; Smith, Aaron; Soulsby, Chris; Sprenger, Matthias; Tetzlaff, Doerthe
Abstract: Root water uptake (RWU) by vegetation influences the partitioning of water between transpiration, evaporation, percolation, and surface runoff. Measurements of stable isotopes in water have facilitated estimates of the depth distribution of RWU for various tree species through methodologies based on end member mixing analysis (EMMA). EMMA often assumes that the isotopic composition of tree‐stored xylem water (δXYLEM ) is representative of the isotopic composition of RWU (δRWU ). We tested this assumption within the framework of EcH2 O‐iso, a process‐based distributed tracer‐aided ecohydrologic model, applied to a small temperate catchment with a vegetation cover of coniferous eastern hemlock ( Tsuga canadensis ) and deciduous American beech ( Fagus grandifolia ). We simulated three scenarios for tree water storage and mixing: (a) zero storage (ZS), (b) storage with a well‐mixed reservoir (WM), and (c) storage with piston flow (PF). Simulating tree storage (WM and PF) improved the fit to δXYLEM observations over ZS in the summer and fall seasons and substantially altered calibrated RWU depths and stomatal conductance. Our results suggest that there are likely to be advantages to considering tree storage and internal mixing when attempting to interpret δXYLEM in the estimation of RWU depths and critical zone water residence times, particularly during periods of low transpiration. Improved representations of tree water dynamics could yield more accurate ecohydrologic and earth system model representations of the critical zone.